Variations in Nutrients Composition of Most Commonly Consumed Cassava (Manihot esculenta) Mixed Dishes in South-Eastern Nigeria - G. I. Davidson; H. N. Ene-Obong; C. E. Chinma (Journal of Food Quality)
Variations in nutrient composition of most commonly consumed cassava (Manihot esculenta) mixed dishes in South-eastern Nigeria were determined. Four communities were randomly selected from each of the five states in the South-east. Focus group discussions (FGD) were conducted in each of the communities to determine commonly consumed foods and variations in recipes. 24-Hour dietary recall was conducted using 50 randomly selected households in those communities. Recipes collected during the FGD were standardized, prepared, and chemically analysed using standard methods. Data were analysed using descriptive statistics. Cassava-based dishes were the most commonly consumed in South-eastern Nigeria. Ninety-two percent of the study population ate cassava either in form of “fufu” (fermented cassava meal)/garri (fermented and roasted cassava meal) with soup or as “abacha” (tapioca salad). Commonly consumed soups were melon (Citrullus vulgaris) seeds, “ora” (Pterocarpus soyauxii), and vegetable soups. Seven melon seed, six “ora,” and four vegetable soups and five “abacha” variations were identified. Except for vegetable soup, coefficient of variation for moisture was <10%, while large variations (19–71%) were observed for energy and nutrients. These variations in cassava-based dishes need to be reflected in the country-specific food composition database to enable nutrient intake assessment or provision of dietary guidance using such food composition database as a reference material to be more effective.